2011
DOI: 10.1002/ijc.25554
|View full text |Cite
|
Sign up to set email alerts
|

Common alleles in candidate susceptibility genes associated with risk and development of epithelial ovarian cancer

Abstract: Common germline genetic variation in the population is associated with susceptibility to epithelial ovarian cancer. Microcell-mediated chromosome transfer and expression microarray analysis identified nine genes associated with functional suppression of tumorogenicity in ovarian cancer cell lines; AIFM2, AKTIP, AXIN2, CASP5, FILIP1L, RBBP8, RGC32, RUVBL1 and STAG3. Sixty-three tagging single nucleotide polymorphisms (tSNPs) in these genes were genotyped in 1,799 invasive ovarian cancer cases and 3,045 controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 41 publications
(45 reference statements)
0
40
3
Order By: Relevance
“…In addition to familial BRCA1 and BRCA2 mutations, there are other kinds of genetic risk factors, including common genetic variants of lower penetrance 2,3 . Molecular epidemiological studies have been conducted with the candidate gene approach to identify low penetrance susceptibility genes for ovarian cancer, many of which have showed inconsistent results [4][5][6][7][8][9][10][11] . Recent genome-wide association studies (GWASs) have reported 11 new singlenucleotide polymorphisms (SNPs) that are associated with ovarian cancer risk in European populations [12][13][14][15][16][17] .…”
mentioning
confidence: 99%
“…In addition to familial BRCA1 and BRCA2 mutations, there are other kinds of genetic risk factors, including common genetic variants of lower penetrance 2,3 . Molecular epidemiological studies have been conducted with the candidate gene approach to identify low penetrance susceptibility genes for ovarian cancer, many of which have showed inconsistent results [4][5][6][7][8][9][10][11] . Recent genome-wide association studies (GWASs) have reported 11 new singlenucleotide polymorphisms (SNPs) that are associated with ovarian cancer risk in European populations [12][13][14][15][16][17] .…”
mentioning
confidence: 99%
“…Based on data from the Cancer Genome Atlas, homologous deletion of AKTIP occurs in multiple cancer lineages including breast (2%), ovary (0.9%), and prostate (1%), consistent with a tumor-suppressor role. However, the functional role of AKTIP could be tumor type-specific, since it has been proposed as a putative oncoprotein in cervical cancer but a tumor suppressor in ovarian cancer (Cinghu et al 2011;Notaridou et al 2011). INHBA encodes inhibin beta A, a subunit of both the activin and inhibin receptors of the transforming growth factor (TGF-beta) superfamily (Risbridger et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…1). Studies published in Finland (43) and Denmark (10) in the past several decades suggest rates comparable to the United States. Among white women, the reported incidence rates for invasive SAC, EAC, and CCC increased during 1978-1998 (44).…”
Section: Risk Factorsmentioning
confidence: 96%